Differential effects of age of acquisition and frequency on memory: evidence from free recall of pictures and words in Turkish. Issue 1 (2nd January 2018) - Raman, Ilhan; Raman, Evren; İkier, Simay; Kilecioğlu, Elçin; Uzun Eroğlu, Dilek; Zeyveli, Şebnem
ABSTRACT: The advantage of processing early over late acquired items in lexical and semantic tasks across a number of languages is well documented. Interestingly contradictory evidence has been reported in recall tasks where participants perform better overall on late acquired items compared to early acquired items in English. Moreover, free recall is modulated by frequency and list type in that studying pure lists of high-frequency words or low-frequency words typically leads to a recall advantage for high-frequency words. This recall advantage either disappears or is reversed when the same items are presented in mixed lists containing both high- and low-frequency items. The current experiment aims to shed light on this discrepancy by exploring the influence of Age of Acquisition (AoA) and frequency on free recall on standardised pictures and their names in Turkish. Eighty Turkish-speaking participants were assigned to either the picture (N = 40) or word condition (N = 40) in which stimuli were presented in either a mixed or a pure list. Following a distractor task, participants were asked to recall as many items as they could remember from the list they viewed. The findings and their implications are discussed within the context of current cognitive frameworks.